Legal methodology and its application to the Law of penalization of violence against women - González Solano, Gustavo (2019)
The Law on Criminalization of Violence against Women presents several legislative errors that generate inconsistencies and injustices with respect to other regulations of the Costa Rican legal system. For this reason, the ENCUIP method is proposed for an approximation to the legal drafting criteria. Keywords: legal methodology, ENCUIP, violence, women